ANALISIS PENERAPAN SIKLUS AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH KABUPATEN PURWOREJO - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2021)
ABSTRACT Small and Medium Enterprises (SMEs ) is a small business units that could play a role and serve as a safety valve in both the supply of alternative productive business activities, alternative lending, and in terms of employment. Micro have an important role in economic development , because the intensity of labor is relatively higher and a smaller investment, so that micro-businesses are more flexible in the face and adapt to market changes . The problem often faced by the SMEs include product marketing, financial limitations, limited human resources, raw material shortages, limitations of the technology, to financial management. Financial management through the application of the accounting cycle is sometimes ignored by the SMEs. This study aims to determine the application of the accounting cycle is carried out at SMEs in Kabupaten Purworejo in generating financial reports . This study uses a survey method that takes a sample of the population using questionnaires. The survey was conducted in Kabupaten Purworejo, with as many as 100 respondents SMEs using descriptive analysis as a tool of analysis . This research resulted in a weighted score of 0.19 which refers to the Guttman scale these figures are in the low 0.00 to 0.25 no association or association ( weak association) which shows that the SMEs in Kabupaten Purworejo not applying the accounting cycle on the financial management of their business . Keywords : Accounting Cycle, SMEs